Orbital Inflammatory Syndrome Post Group A Streptococcal Infection — Case Series and Review of Literature. (2nd January 2019) - Rabina, Gilad; Leibovitch, Igal; Abumanhal, Muhammad; Rosenblatt, Amir; Ben Cnaan, Ran
ABSTRACT: Objective : To report new cases of orbital inflammatory syndrome (OIS) post group A streptococcal (GAS) infection and review the literature. Methods : A retrospective case series of patients with OIS post GAS infection seen in our clinic (from January 2015 to December 2016) and review of additional patients from the literature. Results : A total of nine patients with OIS post GAS infection were included in the study (four patients seen in our clinic and five from previous literature); seven females and two males, three children (under the age of 16), and six adults. Eight patients (89%) presented with a single rectus muscle (5 medial, 3 lateral) myositis, and one (11%) presented with posterior scleritis and diffuse OIS. Conclusions : Although there are very few reports on OIS post GAS infection, it may be more common than previously thought and should be considered in the differential diagnosis of patients with orbital inflammation.